Bases of molecular knowledge of autism with VARS y NRXN1 variants: purpose of a case - Echeverri Chica, Daniela; Moreno Giraldo, Lina Jhoanna (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Background: Autism spectrum disorder (ASD) comprises heterogeneous alterations that compromise neurodevelopment, mainly the ability to communicate and relate to the environment, and do not resolve at any time in life. It presents with multiple profiles and its clinical expression depends on different factors where genetics and environmental factors play a fundamental role. This is an important group of delayed psychomotor development in the pediatric population and despite not having a curative treatment, early identification will allow an early initiation of neurobehavioral therapies, targeted complementary management and appropriate clinical follow-up, improving the prognosis and offering a Specific genetic counseling, carrying out primary prevention strategies, which will impact the burden of disease. Identifying it early makes it easier to find different genetic associations through tests such as next generation sequencing (NGS), constituting a path to develop future therapies. Case presentation: The case of a 5-year-old male patient with delayed psychomotor development due to impaired language is described, in whom three variants of the NRXN1 and VARS2 genes associated with ASD were detected through an NGS test, allowing genetic counseling. adequately and guiding the therapy individually. Results: Using a next-generation sequencing test, three variants of the NRXN1 and VARS2 genes associated with autism spectrum disorder were detected, allowing appropriate genetic counseling, and guiding individualized therapy.